-0.5h-7=-11

Simple and best practice solution for -0.5h-7=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.5h-7=-11 equation:


Simplifying
-0.5h + -7 = -11

Reorder the terms:
-7 + -0.5h = -11

Solving
-7 + -0.5h = -11

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -0.5h = -11 + 7

Combine like terms: -7 + 7 = 0
0 + -0.5h = -11 + 7
-0.5h = -11 + 7

Combine like terms: -11 + 7 = -4
-0.5h = -4

Divide each side by '-0.5'.
h = 8

Simplifying
h = 8

See similar equations:

| 3x-15=7x-75 | | -1/2c-7=-11 | | g-0.25=.625 | | 58.5=3.5x-2 | | 5(x-3)=7x-2(x-1) | | 28d+20=50 | | -.40+14= | | 5(x+1)=3(x+2) | | 3.8x=17-8 | | 3.8=17-8 | | y/5-10=-4 | | 36x^3-6x^2-20x=0 | | 9/n=21/14 | | 15/6=d/4 | | X+5+2*x-3=17 | | y^2-3y=70 | | -(6y+4)-(-5y-7)=2 | | -1=2x+17 | | x/3+12=9 | | X+5+2x(-3)=17 | | 1200=96s^2 | | (6x-4)(3x-4)= | | 275=4.9t^2 | | 15-m/4=28 | | X(x)-7x+12=0 | | 5a/11-3=17 | | m+2m=48 | | 8+(x+2)=6x | | 8=4+4v | | 1/4x-1/8x=3 | | 2/3y+13=4/7y | | B(b)-7b+12=0 |

Equations solver categories